Design of Integrated pH-Water Level Sensors using Arduino Uno-ESP 32 Microcontroller for Integrated Rice-Fish Farming Waste Water Utilization - Dhiya’ulhaq, Syaikha Butsaina; Ramadiani, Haliza; Kaladinanty, Malika Pintanada; Julianto, Mohammad Endy; Indahsari, Siti Rachmi; Suhendra, Ahmad Adi (Waste Technology, 2024)
Integrated Rice-Fish Farming System (IRRFS), a conventional rice, poultry, and fish farming system which is widely practiced in south asia, facing the serious obstacles amidst its advantageous contemption. The main challenge is inharmonious water uptake management as the side effect of its area arrangement and inappropriate water irrigation system due to the lack of technology application, leading to the chemical contamination and high water consumption. This paper develop an integrated pH and water level sensors using combined arduino uno-esp 32 microcontroller for the newly designed IRRFS (mina padi) concept and the new concept of IRRFS in terms of area arrangement restructuration with 1:500 diminution scale, aiming to overcome the pest and chemical contamination to the system and high water amount necessity. The integrated pH-water level sensor is designed to maintain daily water uptake of fish ponds and paddy fields to prevent harvest failure. The integrated sensor will instruct either 1st pump or 2nd pump to drain in or drain off the water from the system. The working accuracy is tested by both calibration and the prototype experiment, resulting in the simultaneity working ability of integrated sensors with 1st pump and 2nd pump which possess with high accuracy.